Rediscovering the relevance of clinical medicine with a case of Chilaiditi’s syndrome (Indian Journal of Case Reports, 2024)
Chilaiditi’s sign is a rare radiological diagnosis characterized by colonic interposition between the diaphragm and the liver, and when symptomatic it is known as Chilaiditi’s syndrome. We report that the case of a 55-years-old male, who was referred to our institution as a case of colitis, with the symptoms of recurrent vomiting, pain abdomen, and altered bowel habit, was eventually diagnosed to have Chilaiditi’s syndrome with non-specific colitis, after carefully taking the history and clinically examining the patient.